Constraints on the sub-pc environment of the nearby Type Iax SN 2014dt from deep X-ray and radio observations. Issue 1 (4th May 2021) - Stauffer, C M; Margutti, R; Linford, J D; Chomiuk, L; Coppejans, D L; Demarchi, L; Jacobson-Galán, W; Bright, J; Foley, R J; Horesh, A; Baldeschi, A
ABSTRACT: We present X-ray and radio observations of what may be the closest Type Iax supernova (SN) to date, SN 2014dt ( d = 12.3–19.3 Mpc), and provide tight constraints on the radio and X-ray emission. We infer a specific radio luminosity $L_R\lt (1.0\!-\!2.4)× 10^{25}\, \rm {erg\, s^{-1}\, Hz^{-1}}$ at a frequency of 7.5 GHz and a X-ray luminosity $L_X\lt 1.4× 10^{38}\, \rm {erg\, s^{-1}}$ (0.3–10 keV) at ∼38–48 d post-explosion. We interpret these limits in the context of Inverse Compton (IC) emission and synchrotron emission from a population of electrons accelerated at the forward shock of the explosion in a power-law distribution $N_e(γ _e)\propto γ _e^{-p}$ with p = 3. Our analysis constrains the progenitor system mass-loss rate to be $\dot{M}\lt 5.0 × 10^{-6} \rm {M_{\odot }\, yr^{-1}}$ at distances $r\lesssim 10^{16}\, \rm {cm}$ for an assumed wind velocity $v_w=100\, \rm {km\, s^{-1}}$, and a fraction of post-shock energy into magnetic fields and relativistic electrons of ϵ B = 0.01 and ϵ e = 0.1, respectively. This result rules out some of the parameter space of symbiotic giant star companions, and it is consistent with the low mass-loss rates expected from He-star companions. Our calculations also show that the improved sensitivity of the next-generation Very Large Array (ngVLA) is needed to probe the very low-density media characteristic of He stars that are the leading model for binary stellar companions of white dwarfs giving origin to Type Iax SNe.